1984
DOI: 10.1177/014107688407701008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Family Relationships on Psychogeriatric Patients

Abstract: Severe strain has been repeatedly reported in the families of psychogeriatric patients. Nevertheless, many families continue to provide a great deal of support, despite the undoubted burden involved. A retrospective study of short-term outcome in 60 psychogeriatric referrals demonstrated the importance of some aspects of the relationship between the patient and their key supporting relative. In the sample as a whole, and in functional patients, the extent to which a positive communication system existed was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
(4 reference statements)
1
9
0
1
Order By: Relevance
“…In addition, conflict in the caring relationship may be a significant risk factor for deterioration of functioning in the person with dementia, and for presentation to services (Bergmann et al, 1984;Orrell and Bebbington, 1995). However, de Vugt et al (2003) found that patient apathy rather than depressive mood was associated with deterioration in the quality of the relationship between patient and caregiver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, conflict in the caring relationship may be a significant risk factor for deterioration of functioning in the person with dementia, and for presentation to services (Bergmann et al, 1984;Orrell and Bebbington, 1995). However, de Vugt et al (2003) found that patient apathy rather than depressive mood was associated with deterioration in the quality of the relationship between patient and caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…This provides a brief assessment of the quality of the caring relationship in three domains: dominance-submissiveness, negative-positive communication, and autonomy-physical dependency rated on seven-point scales. Previous use of the measure indicates satisfactory inter-rater reliability (Bergmann et al, 1984).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study the association might be spurious, since deterioration itself may lead to a poorer quality of relationship. Bergmann et al (1984) also found that a poor outcome in their dementia group was associated with a higher level of physical dependency and a lower level of autonomy. Indeed, some studies have shown that more dependent dementia sufferers may be more manageable and that it is behavioural disturbance which places particular stress on the carer (Isaacs et al, 1972;Gilleard, 1984).…”
Section: Discussionmentioning
confidence: 90%
“…Quality of the relationship with carer. If the subject had a carer who was a cohabitee, a brief assessment of the current state of their relationship was made using the scales developed by Bergmann et al (1984). This method was chosen because it is brief and easy to administer, and because relationship quality according to these scales has been shown to predict outcome in patients with dementia who have carers.…”
Section: The Life Events and Difficulties Schedulementioning
confidence: 99%